1995
DOI: 10.7326/0003-4819-123-5-199509010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Blood Donors with Antibody to Hepatitis C Virus: Clinical, Biochemical, Virologic, and Histologic Features

Abstract: Most blood donors with anti-HCV have chronic hepatitis C regardless of their serum alanine aminotransferase levels. Donors with normal alanine aminotransferase levels and no HCV RNA in their serum generally have normal liver histologic findings or minimal changes and have probably recovered from HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
125
5
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(142 citation statements)
references
References 0 publications
8
125
5
4
Order By: Relevance
“…Of those with HCV infection, 13.2% had undetectable HCV RNA; very similar to that observed in other studies (15-45%) [26,27]. Of note is that the population studied did not have any biochemical evidence of an elevated grade of fibrosis, as had been described previously [28,29].…”
Section: Discussionsupporting
confidence: 73%
“…Of those with HCV infection, 13.2% had undetectable HCV RNA; very similar to that observed in other studies (15-45%) [26,27]. Of note is that the population studied did not have any biochemical evidence of an elevated grade of fibrosis, as had been described previously [28,29].…”
Section: Discussionsupporting
confidence: 73%
“…A subset of patients from the cohort had two liver biopsies performed separated by 6 months or more and without receiving therapy between the two biopsies. This group consisted of 59 blood donors enrolled in a study of the natural history of hepatitis C, 22 52 untreated control patients who were participating in randomized trials evaluating interferon alfa or ribavirin, 23,24 and 30 patients who were referred for evaluation and possible therapy who elected not to undergo treatment. 4 A proportion of these patients were the subject of a previous report on fibrosis; however, steatosis was not specifically analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty five patients (51%) had chronic hepatitis, most of them grading from A1 to A2. Seventeen out of 25 patients (68%) had fibrosis, while other studies reported results ranging from 41% to 90% (22,26) . Interestingly, one of our patients showed cirrhosis.…”
Section: Discussionmentioning
confidence: 60%
“…The frequency of anti-HCV in blood donors varies from about 1% to 2%, according to the geographic area and the population studied (24) . HCV is the pathogen related with 80% to 90% post-transfusional hepatitis (10,26) . In the present study, the main laboratorial alterations occurred in ALT and AST levels that were above normal in 85.7% and 73.5% of the blood donors, respectively (Table 2).…”
Section: Discussionmentioning
confidence: 99%